2016
DOI: 10.1186/s13256-016-0876-9
|View full text |Cite
|
Sign up to set email alerts
|

A 33-year-old patient with human immunodeficiency virus on antiretroviral therapy with efavirenz-induced complex partial seizures: a case report

Abstract: BackgroundEfavirenz is a commonly prescribed antiretroviral drug that is largely well tolerated. However, seizure disorder is a rare side effect. Prompt identification and immediate replacement of efavirenz with an alternative drug would effectively stop the seizures. To the best of our knowledge, we present the first reported case in the literature of complex partial seizures arising due to efavirenz.Case presentationWe report a case of a 33-year-old Nigerian man treated with an efavirenz-based antiretroviral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Public health programs, especially the HIV/AIDS, Tuberculosis and Malaria have the greatest risk of ADRs because millions of people are treated with a wide range of drugs, some of which have serious/life threatening adverse reactions [ 35 38 ]. In the western countries where ARVs have been used for many years, cases of rising obesity, weight gain and cardio-metabolic diseases are persistently being reported in association with the use of ARVs [ 39 40 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Public health programs, especially the HIV/AIDS, Tuberculosis and Malaria have the greatest risk of ADRs because millions of people are treated with a wide range of drugs, some of which have serious/life threatening adverse reactions [ 35 38 ]. In the western countries where ARVs have been used for many years, cases of rising obesity, weight gain and cardio-metabolic diseases are persistently being reported in association with the use of ARVs [ 39 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Until the SPHAR-TI course, majority (71.0%) of the healthcare workers that participated in the course have never received training in pharmacovigilance but were nonetheless working in public health institutions or hospitals directly treating HIV/AIDS, Tuberculosis and Malaria through the respective public health disease control programs. Some studies have reported high prevalence of ADRs emanating from the HIV/AIDS, TB and Malaria public health programs [ 13 , 35 , 37 , 38 , 39 , 40 ], thus, justifying the SPHARTI model.…”
Section: Introductionmentioning
confidence: 99%